Tinjauan Yuridis Terhadap Perjanjian Jual Beli Online Dengan Jasa M- Bangking - Nafturahma , Nadya AL; Safitri , Latipah Nurma; Parolita, Inka; Dania , Rahma; Sari , Yetri Oktiva (Jurnal Kewirausahaan & Inovasi, 2024)
This study aims to find out what the legal standing is for online buying and selling agreements through M-banking and to find out what the legal consequences are for online buying and selling fraud. The research method used in this research is normative research with descriptive research type. The approach used is a statutory approach (statue approach) and a doctrinal/conceptual approach. The type of data used is secondary data which consists of primary legal materials, secondary legal materials, and tertiary legal materials. Data collection was carried out by means of a literature study. Then the collected data were analyzed systematically. According to the results of this study, it shows that: First, online buying and selling agreements in buying and selling forums through M-banking services fulfill the legal requirements of an agreement in accordance with the provisions of Article 1320 of the Criminal Code, which states that part of one of the legal requirements of an agreement is that there is an "agreement of those who bind himself”. Although there is one of the legal requirements of the agreement that is not fully met, namely regarding the skills requirements of the parties. However, the online sale and purchase agreement in the buying and selling forum through joint account services remains valid and binds the parties involved in it and becomes law for the parties who carry it out. The terms of competence of the parties are subjective requirements which if these conditions are not fully met in an agreement does not cause the agreement to become invalid, but only the agreement can be canceled by one of the parties. Second, the legal consequences of fraud in online buying and selling agreements in Indonesian positive law, namely giving rise to responsibility for consumer losses in transactions for consumer losses oblige the person who because of the mistake of issuing the loss, compensates for the loss. The consequences of online buying and selling fraud not only have legal consequences but also in the realm of civil and criminal law.